ANALISIS PROBLEM STRUCTURING SECARA BERTINGKAT PROGRAM REVITALISASI POSYANDU DI KECAMATAN WONOKERTO KABUPATEN PEKALONGAN - Yuniarti .; Nur Susanti (LPPM Universitas Pekalongan, 2011)
The purpose of this study is to arrange the structuring problems of Posyandu revitalization program. The method of the study is stepping qualitative analysis method; problems finding, problems grouping, problems specification, and problems understanding. The method of collecting data used is hierarchy method in each problem. The research informant is the head of Wonokerto Public Health Center and Posyandu representative in random sampling. The units of analysis are the time series of Posyandu in the last three years, the result of the interview with the informant, and the result of observation in Posyandu services. The result of the study shows that the structuring revitalization program consists of three aspects; input, process, and out put. In the aspect of input shows that the number of Posyandu representative is increasing by the integration of representative groups, almost all Posyandu have facilities and adequate amount of medicine to support the services, all of Posyandu representative have been trained but the activeness is still law, the public funding can support the work of Posyandu, the other support by Universities, and PKK participation. In the aspect of process shows that the number of representative trainings has increased, there are only basic services and there is no additional service, the involvement of public is not significant but the number of visit has increased, and the survey of children growth is held by Posyandu representative. The aspect of out put shows that the increasing of diseases problems finding by the house visitation, such as; ISPA, mal-nutrient, and hydrocephalus.Key words: Stepped Structuring Problems, Posyandu Revitalization Problems